Special education teachers in training and ethical competence development. An exploration at the University of Sassari - Paolo Calidoni; Filippo Dettori; Giusy Manca; Luisa Pandolfi (Firenze University Press, 2021)
In school contexts, ethical competences are crucial in order to make the teacher able to manage the class dynamics and the relationships with families and colleagues. These competences are all the more necessary to the special education teacher. These competences are neither specified nor defined at regulatory and teacher training level; nevertheless, they are transversally present in many of the skills required to the special education teacher. This paper describes an exploratory research carried out at the University of Sassari in the context of a national research project on moral education in lower secondary school. The aforementioned exploratory research aims to assess the point of view of special education teachers during their training, in order to define adequate training strategies for the development of ethical, reflective and argumentative skills. On the basis of the results, guidelines were set for a training course that is being currently in test phase.   Insegnanti di sostegno in formazione e sviluppo della competenza etica. Un'esperienza presso l'Università di Sassari Nel contesto scolastico la competenza etica dell'insegnante si configura come una competenza molto importante per la gestione delle dinamiche della classe e dei rapporti con le famiglie e con i colleghi. Particolare rilevanza assume per l'insegnante specializzato per le attività di sostegno didattico agli alunni con disabilità. I decreti ministeriali non individuano in modo esplicito questa competenza, che appare come trasversale a molte delle abilità considerate centrali per il profilo dell'insegnante di sostegno. Il presente contributo descrive una ricerca esplorativa realizzata presso l'Università di Sassari, nell'ambito di un PRIN sull'educazione morale nella scuola secondaria di primo grado, che ha la finalità di ascoltare il punto di vista degli insegnanti di sostegno in formazione per definire adeguate strategie formative per lo sviluppo di competenze etiche, riflessive ed argomentative. Gli esiti emersi sono alla base di un percorso formativo in corso di 'prova' sul campo.